Attachment: Theoretical aspects and research possibilities - Čekuolienė, D. (Psichologija, 1991)
The aim of this paper is to present a short review of the works in the field of attachment. Various theoretical approaches treat attachment in a different way. One of the best known and extensively accepted approach to this question is J. Bowlby's attachment theory which lies on the principles derived from ethology. Bowlby's approach to attachment has been adopted with notable success by his colleague Mary Salter Ainsworth, who offered a very productive procedure for the empirical investigations in this field called the Strange Situation Method. The main conclusion drawn from her studies is that the type of attachment depends on mother's sensitivity and responsiveness to young child signals during infancy. It may cause secure and insecure relationships between the mother and the infant. The last part of present paper deals with current researches and the most actual questions in attachment including the possibilities of such work in Lithuania.
Keywords: attachment; attachment theory; Bowlby; Ainsworth